2014
DOI: 10.3892/mmr.2014.2771
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene protects against apoptosis in hypoxia/reoxygenation-induced H9C2 myocardioblast cells through increased autophagy

Abstract: Lycopene (Ly), the most common type of antioxidant in the majority of diet types, provides tolerance to ischemia/reperfusion injury. However, the underlying mechanism of the protective effects observed following Ly administration remains poorly investigated. The aim of the current study was to investigate whether Ly prevents damage to hypoxia/reoxygenation (HR)‑induced H9C2 myocardioblasts in an autophagy‑dependent manner. The levels of autophagic markers were detected using western blotting, the level of apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
1
18
1
Order By: Relevance
“…In addition, previous studies showed that Ca 2+ concentration, autophagy, and redox regulation are linked to neurotoxicity as stated elsewhere. LYC treatment improves cell viability and reduces apoptosis as a result of the activation of the adaptive autophagic response on HR induced H9C2 myocardioblasts [ 64 ]. In the future study, we will focus on unveiling the inherent associations of Cd-induced Ca 2+ homeostatic change, redox stress and autophagy activation to Cd-triggered hippocampal neurotoxicity; also, we will further optimize the LYC dietary treatment in order to initiate the clinical based study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies showed that Ca 2+ concentration, autophagy, and redox regulation are linked to neurotoxicity as stated elsewhere. LYC treatment improves cell viability and reduces apoptosis as a result of the activation of the adaptive autophagic response on HR induced H9C2 myocardioblasts [ 64 ]. In the future study, we will focus on unveiling the inherent associations of Cd-induced Ca 2+ homeostatic change, redox stress and autophagy activation to Cd-triggered hippocampal neurotoxicity; also, we will further optimize the LYC dietary treatment in order to initiate the clinical based study.…”
Section: Discussionmentioning
confidence: 99%
“…54,56,57,[202][203][204] Lycopene has a protective effect against neurological disorders including Alzheimer's and PD by reducing oxidative stress. [205][206][207][208][209][210][211] Lycopene supplementation of a rotenone-induced rat model of PD enhances the protective effect against oxidative stress and reduces neurobehavioral abnormalities.…”
Section: Nanolycopenementioning
confidence: 99%
“…Lycopene, a member of the carotenoid family, is found predominantly in tomatoes and other red colored fruits (8). It has been reported that lycopene protects against apoptosis in hypoxia/reoxygenation-induced H9C2 myocardioblast cells (34). In addition, He et al (35) reported that lycopene attenuates inflammation and apoptosis in postmyocardial infarction remodeling.…”
mentioning
confidence: 99%